2022
DOI: 10.3389/fpls.2022.857390
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-Wide Characterization of Seed Aging in Rice: Identification of Specific Long-Lived mRNAs for Seed Longevity

Abstract: Various long-lived mRNAs are stored in seeds, some of which are required for the initial phase of germination and are critical to seed longevity. However, the seed-specific long-lived mRNAs involved in seed longevity remain poorly understood in rice. To identify these mRNAs in seeds, we first performed aging experiment with 14 rice varieties, and categorized them as higher longevity (HL) and lower longevity (LL) rice varieties in conventional rice and hybrid rice, respectively. Second, RNA-seq analysis showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The detrimental effects of high-temperature stress on seed germination chiefly manifest in the diminished germination rate and vigor, undermining the seed antioxidant defense and the synthesis of osmotic-adjustment compounds ( Hussain, Farooq & Lee, 2017 ; Shu et al, 2018 ; Sharma & Zheng, 2019 ). Many studies have proven that high temperature stress significantly inhibits seed germination of chickpea genotypes ( Adishesha & Chimmad, 2021 ), rice ( Wang et al, 2022 ), and beans ( De Santis et al, 2021 ). In this research, five kinds of buckwheat seed growth indicators and germination were reduced by a high temperature of 28 °C—highlighting the adverse effects of high-temperature stress on buckwheat seed germination ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The detrimental effects of high-temperature stress on seed germination chiefly manifest in the diminished germination rate and vigor, undermining the seed antioxidant defense and the synthesis of osmotic-adjustment compounds ( Hussain, Farooq & Lee, 2017 ; Shu et al, 2018 ; Sharma & Zheng, 2019 ). Many studies have proven that high temperature stress significantly inhibits seed germination of chickpea genotypes ( Adishesha & Chimmad, 2021 ), rice ( Wang et al, 2022 ), and beans ( De Santis et al, 2021 ). In this research, five kinds of buckwheat seed growth indicators and germination were reduced by a high temperature of 28 °C—highlighting the adverse effects of high-temperature stress on buckwheat seed germination ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the degradation of long mRNAs is stronger in aged seeds [6,33]. Other studies focused on RNA degradation including seed water content [34], RIN (RNA integrity number) [7,35], transcriptome and gene expression levels [9,22]. This makes mRNA associated processes a focal point in seed storage studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, with the early identification of seed deterioration based on molecular techniques, for example, and with a reduced input of samples, it can significantly contribute to the maintenance of stocks, implying less need for new collections in nature. The study of gene expression among seeds with natural or accelerated aging shows similar results at transcriptional levels, with differences for small numbers of genes between varieties that are sensitive or more tolerant to ageing [22]. Thus, several studies have analyzed the gene expression profile with a focus on development in order to identify possible genes responsible for the aging process in order to detect the beginning of the decline in seed viability [9,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Similar conclusions were drawn from a study in Arabidopsis, leading to an estimate of mRNA damage in the dry seed at a rate of ∼1 × 10 −4 per nucleotide per day, equating to each nucleotide in a transcript suffering damage once every 30 years [ 69 ]. In rice, natural ageing and accelerated ageing resulted in similar transcriptional changes in the dry seed, with mRNA degradation occurring at higher rates in a subset of transcripts [ 70 ]. These results are consistent with previous reports showing targeted RNA degradation in desiccated seeds [ 67 ].…”
Section: Rna Modificationmentioning
confidence: 99%